Identification of novel targets of miR-622 in hepatocellular carcinoma reveals common regulation of cooperating genes and outlines the oncogenic role of zinc finger CCHC-type containing 11 - Gaza, Anne; Fritz, Valerie; Malek, Lara; Wormser, Laura; Treiber, Nora; Danner, Johannes; Kremer, Andreas E.; Thasler, Wolfgang E.; Siebler, Jürgen; Meister, Gunter; Neurath, Markus F.; Hellerbrand, Claus; et al. (Neoplasia, 2021)
The poor prognosis of advanced hepatocellular carcinoma (HCC) is driven by diverse features including dysregulated microRNAs inducing drug resistance and stemness. Lin-28 homolog A (LIN28A) and its partner zinc finger CCHC-type containing 11 (ZCCHC11) cooperate in binding, oligouridylation and subsequent degradation of tumorsuppressive let-7 precursor microRNAs. Functionally, activation of LIN28A was recently shown to promote stemness and chemoresistance in HCC. However, the expression and regulation of LIN28A in HCC had been unclear. Moreover, the expression, regulation and function of ZCCHC11 in liver cancer remained elusive. In contrast to "one-microRNA-one-target" interactions, we identified common binding sites for miR-622 in both LIN28A and ZCCHC11, suggesting miR-622 to function as a superior pathway regulator. Applying comprehensive microRNA database screening, human hepatocytes and HCC cell lines, patient-derived tissue samples as well as "The Cancer Genome Atlas" (TCGA) patient cohorts, we demonstrated that loss of tumorsuppressive miR-622 mediates derepression and overexpression of LIN28A in HCC. Moreover, the cooperator of LIN28A, ZCCHC11, was newly identified as a prognostic and therapeutic target of miR-622 in liver cancer. Together, identification of novel miR-622 target genes revealed common regulation of cooperating genes and outlines the previously unknown oncogenic role of ZCCHC11 in liver cancer.
CRIS-Team Scopus Importer:2021-05-07
Keywords: drug resistance; HCC; Hepatocellular carcinoma; microRNA; ZCCHC11